Eucommia, Cuscuta, and Drynaria Extracts Ameliorate Glucocorticoid-Induced Osteoporosis by Inhibiting Osteoclastogenesis Through PI3K/Akt Pathway - Han, Junwen; Li, Li; Zhang, Chen; Huang, Qianqian; Wang, Shanglong; Li, Wenyu; Zong, Jiancheng; Li, Lijie; Zhao, Zhen; Zhang, Zengliang; Liu, Zimin; Wang, Qi; et al. (Frontiers in Pharmacology, 2022)
Osteoporosis is one of the most common diseases in the world which resulted in heavy socioeconomic burden and public health threat. Glucocorticoid-induced osteoporosis (GIO) is the most common secondary reason of osteoporosis. Therapeutic strategies using traditional Chinese medicine are under investigation for osteoporosis, with efforts to improve efficacy and clarify the mechanism. The combination of Eucommia, Cuscuta and Drynaria is widely used in traditional Chinese decoction for osteoporosis treatment, but the experimental efficacy and mechanism are still unclear. Administration of E.C.D extracts (Eucommia, Cuscuta and Drynaria) in experimental GIO rats resulted in decreased urinal calcium, phosphorus loss and decreased expression of RANKL, CTX in serum, increased serum calcium, phosphorus and OPG level. E.C.D extracts also improved bone density, structural integrity and biomechanical function in experimental GIO rats. These finding were associated with E.C.D extracts’ treatment efficacy to GIO in vivo. The balance between osteoclast and osteoblast activity is essential for bone remodeling and bone related disease. The E.C.D extracts inhibited Raw 264.7 cell differentiation to osteoclast in vitro. On the other hand, it promoted OPG expression of bone marrow mesenchymal stromal cells (MSCs) which can suppress the osteoclast genesis. E.C.D extracts also increased the Wnt1, Runx2 expression which are related to osteoblast formation. It also regulated the paracrine effect of MSC to inhibit osteoclast differentiation. The analysis of HPLC and comprehensive pharmacology identified the constituents of E.C.D extracts and the potential osteoporosis-related targets mediated by E.C.D extracts. The KEGG enrichment analysis suggested that PI3K/Akt pathway may be involved in the regulation osteoclast genesis by E.C.D extracts and the result of western blot of vitro assays proved it. Collectively, these data demonstrate E.C.D extracts can inhibit osteoclast differentiation to foster experimental osteoporosis both in vivo and vitro and it may exert the function of inhibiting osteoclast differentiation through PI3K/Akt pathway.